Managers’ national culture and its impact on response styles in a global multinational company - Mutschink, John M (Kansas State University, 2007)
Corporations spend tens of millions of dollars each year to conduct organizational surveys and report the results. It is imperative that survey results provide clear, actionable results to organizational leaders for an employee survey program to be effective. To the extent that survey results are impacted by response style biases, organizations cannot be certain their actions address real issues. The following research examines the impact of managers' national culture on the response styles of their employees. Power distance is a construct that reflects how different cultures address inequality. In this study, power distance scores for managers are hypothesized to be predictive of employee response style behavior such that power distance is positively associated with greater extreme responding and lower acquiescence. Additionally, individualism/collectivism scores for managers are hypothesized to be predictive of employee response style behavior such that individualism is positively associated with greater extreme responding and negatively associated with acquiescence. Overall, results did not support the key hypotheses of the study. While employees from high power distance countries did display higher levels of extreme responding than employees from low power distance countries (Hypothesis 1), none of the other three hypotheses were supported. Despite this lack of significant results, this single result supports Johnson, et al.'s (2005) results from a sample of over eighteen-thousand employees in nineteen countries suggesting it is a consistent, real difference between high and low power distance countries. There were several limitations to be considered in evaluating this research. First, the study was based on archival data limiting the flexibility of the design and analysis. Another key limitation that should be addressed in future research is the use of abstracted cultural trait scores. Despite the lack of significant results and the limitations of this study, the fact remains that differences in response behaviors do exist across different cultures and geographic locations. Further research is needed to more clearly understand the influence that geographic culture, organizational culture and individual level demographics may have on employee response styles to help facilitate how organizations understand survey results.
Keywords: Response styles; Culture; Psychology, Industrial (0624)